Problematika Penggunaan Gimkit Sebagai Media Pembelajaran Interaktif Untuk Siswa di Kelas Tinggi - Khasanah, Aulia Fajar; Sari, Indah Dewi Eka (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to identify and analyze the problematic use of Gimkit as an interactive learning media in elementary school high class. The research method used is descriptive qualitative with Case Study approach. Subjects consisted of teachers and students of Class V in SDN Paron 1. Data were obtained through interviews, observations, and documentation. The results showed that although Gimkits can increase student engagement and motivation to learn, there are a number of obstacles faced, such as limited devices and internet networks, variations in students ' digital literacy skills, and limited time for integration in the curriculum. This study recommends teacher training and technology infrastructure support as the first step to optimize the utilization of Gimkit.